Penyuluhan dan pelatihan kewirausahaan sebagai upaya peningkatan intensi berwirausaha pada UKM ”Bangkit” - Surahma Asti Mulasari; Fatwa Tentama; Sulistyawati; Tri Wahyuni Sukesi; Herman Yuliansyah; Lu'lu' Nafiati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Covid-19 has had a major impact on all aspects of life and in all fields. Since Covid-19 was declared a pandemic, there have been many impacts of Covid-19 and the most pronounced impact has been on the Small and Medium Enterprises (SME) sector. The aim of this program is to provide counseling and training to increase entrepreneurial intentions in “Rise” SMEs in the midst of the Covid-19 pandemic. The target of this program is the people of Ngoro-Oro village who are members of UKM "Bangkit". The method used is in the form of counseling, training and direct practice (role play). Implementation of training for two days. The first day was in the form of counseling and entrepreneurial intention training which consisted of two sessions. The second day was the practice of processing local food ingredients into various types of food such as various kinds of chips (cassava chips, banana chips, spinach chips, etc.), various cakes such as bika and several types of brownies. The result of the program is that the community becomes aware of the concept of entrepreneurship, has the intention or desire to become entrepreneurial and has skills in processing local food ingredients into food products that have sale value